Types according to sentence structure - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
The semantic structure of a sentence is studied by semantic syntax. In traditional syntactic theories, mainly the formal structure of a sentence and the structure of simple sentences, as well as the issue of intonation in these simple sentences are studied separately. Only in some places has the semantics of simple sentences been addressed. Neither the semantic nature and structure of the sentence, nor the semantic types of the sentence, nor the relationship between the formal and semantic structures of the sentence were considered the subject of special study until recent years. In this article, opinions and comments are made on the structure of simple sentences and their intonation. Keywords: simple sentences, intonation, sentence expression, thought, and logical meaning are the structure of a sentence.